Pancreatico-biliary pathologies: correlation of USG and MRCP - Khopde, Priyanka Ashok; Kelkar, Abhimanyu; Joshi, Priscilla; Bandgar, Amol; Mahajan, Mangal (International Surgery Journal, 2019)
Background: Obstructive jaundice is the most frequent form of hepato-biliary pathologies. The main aim is to confirm the presence of obstruction and to identify its cause, location and extent of the lesion. This study evaluated the role of USG and MRCP in hepato-biliary pathology. Methods: Twenty-five patients of all age groups with suspicion of obstructive jaundice referred for Ultrasound were included in our study. The patients with findings suggestive of biliary obstruction underwent MRCP. Results: Out of 25 patients, maximum patients were in the age group of 61-80 yrs. 52% were male and 48% were female. The jaundice was due to a benign etiology in 64% patients and malignant etiology in 36%. The most common benign pathology was choledocholithiasis (25%) and malignant pathology was periampullary carcinoma (44%). Overall 11 cases were inconclusive on ultrasound study while 2 cases were false positive for malignancy on MRCP. In 92% cases the correct diagnosis was detected on MRCP. Conclusions: USG is the initial and sometimes the only imaging modality in obstructive biliary disease. However the distal CBD which is poorly seen on USG can be well evaluated on MRCP thus improving the diagnosis in pancreatico-biliary pathologies.